UNILATERAL TERMINATION OF EMPLOYMENT BY EMPLOYEES AT MOREST RESTAURANT - Ni Putu Ika Candra Dewi; I Made Dedy Priyanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
Getting a job and achieving a decent living is a fundamental right of every citizen. In practice, however, various issues arise in the realm of employment, one of which is related to wages. This wage issue emerges due to a fundamental gap between the regulations aspired to and their implementation in society, often described as the gap between das Sollen and das Sein. This discrepancy is evident in the ineffective enforcement of the law within the community, particularly regarding the Bali Governor's Decree Number 2235/03-G/HK/2019, which pertains to the provision of minimum wages for workers, and the factors that hinder the realization of these minimum wages. The aim of this journal is to analyze and understand the implementation of legal arrangements related to the provision of minimum wages for workers, as well as the factors that impede this implementation. The method employed in this journal is empirical legal research, which is conceptualized as an empirical phenomenon that compares existing rules with their actual implementation or reality in society (das Sollen and das Sein). The findings suggest that the implementation of legal arrangements related to the provision of minimum wages for workers in the Commanditaire Vennootschap (CV) Raka Bali has not been effective. The factors contributing to the ineffectiveness of wage implementation are primarily internal to the company itself.